Mesoscale Convective Complex Verification on Heavy Rain in Semarang (Case Study: 13 March 2024) - Didik Kurniawan; Binsar Hakim Aritonang; Helena Yaku; Imma Redha Nugraheni (Departement of Physics Faculty of Mathematics and Natural Sciences, and Institute of Research and Community Services Udayana University, Kampus Bukit Jimbaran Badung Bali, 2025)
This study aims to identify the Mesoscale Convective Complex (MCC) pattern during a heavy rain event in Semarang City on March 13, 2024, using Himawari-9 satellite imagery. The analysis was based on Maddox's (1980) criteria, including cloud coverage, duration, and convective system eccentricity. The results show that MCC met the requirements with a 7-hour duration, a maximum eccentricity of 0.9498, and shield and core areas of 108,228 km² and 89,128 km², respectively. MCC produced moderate to extreme rainfall intensities, peaking at 60–70 mm/h. MCC activity began in Semarang and moved southwestward, posing hydro-meteorological disaster risks such as flash floods. This study emphasizes the importance of MCC monitoring for hydro-meteorological disaster mitigation in Indonesia.